An Overview of Macroprudential Policy Tools - Claessens, Stijn (Washington, D.C. : International Monetary Fund, 2014)
Macroprudential policies - caps on loan to value ratios, limits on credit growth and other balance sheets restrictions, (countercyclical) capital and reserve requirements and surcharges, and Pigouvian levies - have become part of the policy paradigm in emerging markets and advanced countries alike. But knowledge is still limited on these tools. Macroprudential policies ought to be motivated by market failures and externalities, but these can be hard to identify. They can also interact with various other policies, such as monetary and microprudential, raising coordination issues. Some countries, especially emerging markets, have used these tools and analyses suggest that some can reduce procyclicality and crisis risks. Yet, much remains to be studied, including tools' costs ? by adversely affecting resource allocations; how to best adapt tools to country circumstances; and preferred institutional designs, including how to address political economy risks. As such, policy makers should move carefully in adopting tools.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet